2022
DOI: 10.1186/s12931-022-02164-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic changes related to airway inflammation, asthma pathogenesis and systemic activity following inhaled fluticasone furoate/vilanterol: a randomized controlled trial

Abstract: Background Fluticasone furoate/vilanterol trifenatate (FF/VI) is an inhaled therapy for the treatment of asthma, with a prolonged duration of anti-inflammatory and bronchodilatory action. This study investigated the global metabolomic and lipidomic profile following treatment with FF/VI or placebo and assessed whether changes correlated with exhaled nitric oxide levels as a measure of airway inflammation. Methods This was a single-center, randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…An initial attempt to examine how the microbiome changes alter the metabolite profile with PiCRUSt analysis, showed no significant effect in the low biomass environment of the lung, but significant changes in specific pathways in the gut microbiome of Flut‐treated animals. Interestingly, several the amino acid biosynthetic pathways were upregulated and is consistent with recent metabolite observations in asthma patients (Daley‐Yates et al, 2022 ; Durack et al, 2017 ). One pathway in particular, tyrosine metabolism, is often altered during inflammatory disease (Vacca et al, 2020 ; Zhao et al, 2022 ; Zheng, Parra‐Izquierdo, et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…An initial attempt to examine how the microbiome changes alter the metabolite profile with PiCRUSt analysis, showed no significant effect in the low biomass environment of the lung, but significant changes in specific pathways in the gut microbiome of Flut‐treated animals. Interestingly, several the amino acid biosynthetic pathways were upregulated and is consistent with recent metabolite observations in asthma patients (Daley‐Yates et al, 2022 ; Durack et al, 2017 ). One pathway in particular, tyrosine metabolism, is often altered during inflammatory disease (Vacca et al, 2020 ; Zhao et al, 2022 ; Zheng, Parra‐Izquierdo, et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“… 47 A handful of studies have identified that abnormal mitochondrial β-oxidation contributed substantially to several aspects of asthma, including pathogenesis, disease severity, therapy response, etc. 32 48 49 Al-Khami et al . 50 showed that carnitine palmitoyltransferase 1 (CPT1), a key fatty acid oxidation enzyme, in lung was markedly upregulated in ovalbumin (OVA)-induced murine model of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The authors revealed 22 different metabolites in the serum and 21 metabolites in the urine of budesonide + salbutamol treated asthmatic children compared with asthmatic children treated with a placebo, suggesting reprogramming in seven metabolic pathways: arginine and proline metabolism; taurine and hypotaurine metabolism; glycine, serine and threonine metabolism; glyoxylate and dicarboxylate metabolism; methane metabolism; citrate cycle; and pyruvate metabolism [ 175 ]. On the other hand, treatment of adult asthmatics with inhaled fluticasone furoate/vilanterol trifenatate was accompanied by only subtle systemic metabolomic and lipidomic changes [ 176 ].…”
Section: Metabolomics In Asthmamentioning
confidence: 99%